Isolated Traumatic Sutural Diastasis in a Young Adult: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
The bony calvarium protects the most vital organ of our body.The skull is composed of  various bones united by a zigzag line called sutures.The fusion of these sutures creates the  protective calvarium of the brain.In addition to protection, this suture line helps during  parturition. When the anterior and posterior fontanelle attaches via a fibrous sheet, it has a  favorable shape during vaginal delivery and helps in the development of the brain.The suture  fuses with the adjacent bones at certain ages and creates a protective calvarium.During this  period, suture diastasis occurs due to various causes, such as RTA, falls, and increased  intracranial pressure.It is usually associated with an additional fracture line; however, under
Keywords: Head injury; Skull fracture; Sutural diastasis